Stress analysis of thin-walled laminated composite beams under shear and torsion - Syed Mohamed Ali, Jaffar; Hrairi, Meftah; Masturah, Mohamad (Deer Hill Publications, 2018)
An educational software which can aid students in the stress analysis of thin wall open sections made of composite material has been developed. The software enables students to easily calculate stresses in different shapes of thin walled open section and evaluate the stresses in each ply under shear and torsion. Results obtained through this software have been validated against ANSYS. The software is intended to be an educational tool for effective teaching and learning process on thin-walled structures, aircraft structures and composite structures courses.